ENGLISH LESSON PLAN IMPLEMENTATION BY TEACHERS CANDIDATE IN MICRO TEACHING COURSE AT FKIP OF HKBP NOMMENSEN UNIVERSITY - Silalahi, Dumaris E (UNDIKMA Mataram (Eks. IKIP Mataram), 2020)
English lesson plan is a set of learning plans contains essential guidance for the teacher referring to English teaching material. Successful teaching is not determined by the learners? achievement but also teaching process, which is prepared well by the teacher. It is the proof of teaching as transferring the knowledge. Referring to this case, this research was intended to find out the extent of the English lesson plan implementation by the teacher candidates of English department students as the learner of English as a foreign language. The implementation was observed engaging 65 students who were attending a microteaching class which was one of education compulsory and requirement subject at FKIP of HKBP Nommensen University. Quantitative research design was used to find out the extent of implementation English Lesson plan of the subject. The research found the level of the implementation at 15,19% at level of high, 27,69 % of moderate, 25,00% at low, and 32,11 of poor. It indicates that the English lesson plan implementation by the teacher candidates as the sample in this research was still low.